2021
DOI: 10.7717/peerj.11436
|View full text |Cite
|
Sign up to set email alerts
|

Mahalanobis distances for ecological niche modelling and outlier detection: implications of sample size, error, and bias for selecting and parameterising a multivariate location and scatter method

Abstract: The Mahalanobis distance is a statistical technique that has been used in statistics and data science for data classification and outlier detection, and in ecology to quantify species-environment relationships in habitat and ecological niche models. Mahalanobis distances are based on the location and scatter of a multivariate normal distribution, and can measure how distant any point in space is from the centre of this kind of distribution. Three different methods for calculating the multivariate location and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Recent studies have suggested that modeling approaches based on elliptical envelopes may be more appropriate when the goal is to estimate the fundamental niche of a species (Soberón and Peterson, 2020; Etherington, 2021); while the realized niche may be modeled through more complex shapes (Jiménez-Valverde et al, 2008). On the other hand, it is well known that the CH approach is sensitive to outliers, which may be common in presence-only samples even after going through standard data cleaning procedures.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have suggested that modeling approaches based on elliptical envelopes may be more appropriate when the goal is to estimate the fundamental niche of a species (Soberón and Peterson, 2020; Etherington, 2021); while the realized niche may be modeled through more complex shapes (Jiménez-Valverde et al, 2008). On the other hand, it is well known that the CH approach is sensitive to outliers, which may be common in presence-only samples even after going through standard data cleaning procedures.…”
Section: Methodsmentioning
confidence: 99%
“…From the long list of methods to estimate convex hypervolumes used in SDM and ENM, the following stand out: ( 1 ) convex hulls or polyhedra surrounding all the occurrences (Broennimann et al, 2007; Cornwell et al, 2006; Dallas et al, 2017; Walker and Cocks, 1991); ( 2 ) elliptical envelopes which may contain all or a portion of the occurrences (Swanson et al, 2015; Etherington, 2021), and ( 3 ) hyper-rectangles or box-shaped approaches (Busby, 1991; Nix et al, 1986). It has been shown that there is no clear “best” way to delineate hypervolumes (Blonder, 2018; Merow et al, 2014) and the choice of an appropriate method will depend on the goals of the analysis and data limitations (Blonder et al, 2018; Etherington, 2021; Peterson et al, 2011). The convex hull (CH) approach uses all observations to build the minimum convex polyhedron that contains them.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper uses the average value within the grade to fill the missing parameters for the data with missing parameters considering the scarcity of sample data. At the same time, to minimize the influence of outliers on the model, the Mahalanobis distance method 27 is used to detect outliers, and samples detected as outliers at a confidence level of 0.5% are eliminated. After processing, 60 groups of data samples are obtained, as shown in attached Table 2 .…”
Section: Data and Data Preprocessingmentioning
confidence: 99%